Free Riding and Workplace Democracy—Heterogeneous Task Preferences and Sorting - Kamei, Kenju; Markussen, Thomas (Management Science, 2023)
A novel laboratory experiment is used to show that mismatching between task preferences and task assignment strongly undermines worker performance and leads to free riding in teams. Unlike prior experiments using real effort tasks, task preferences are elicited from all workers. Under team-based remuneration (revenue sharing), free riding is significant, but this effect is largely driven by those working on undesired tasks. Workers’ endogenous sorting into tasks improves productivity as it mitigates task mismatching although workers’ task selection per se has only small effects on work performance and effort provisions beyond the positive sorting effects. This paper was accepted by Yan Chen, behavioral economics and decision analysis. Funding: This work was supported by Independent Research Fund Denmark [Grant 4182-00163]. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2022.4556 .